European insolvency law : reform and harmonization - McCormack, G. (Edward Elgar Publishing, 2017)
Critically analysing the substantive law of insolvency in the EU countries as a whole, this book carries out horizontal cross-cutting analysis of the data gathered from a study of national insolvency laws. It selects particular areas for detailed discussion and considers the pros and cons of particular legislative solutions. Using the US and Norway as comparator countries, the expert authors identify areas where disparities in national laws produce problems that have impacts outside national boundaries. They analyse these against key policy goals including: improving economic performance throughout the EU; promoting a more competitive business environment; efficient asset allocation; and building more stable and sustainable human capital in terms of support for entrepreneurs and responses to consumer over-indebtedness. The book also considers possible reform and harmonization measures situated against the wider contextual background of the Capital Markets Union and the Europe 2020 agenda of promoting jobs and growth. Discerning and practical, European Insolvency Law will appeal to academics in both insolvency and finance as well as insolvency practitioners and lawyers. Its reform suggestions will be of interest to EU Member States' government departments, while also providing a useful reference for consumer associations and debt charities.